Implicatiile & dimensiunea fenomenului rezistentei la produsele antiinfectioase a.u.v. in Romania - Cristina Romeo-Teodor (Medicamentul Veterinar, 2022)
The PPT presentation continues the activity of informing and training specialists in the field of veterinary medicine. The main aspects of the elements that stimulated the development of Antimicrobial Resistance (AMR), the evolution of the measures taken in the EU are presented. and Romania's connection to them, which is PCU (Population Correction Unit), about the sales rate by categories of products and drug groups in EU and Romania, ways and mechanisms of development of RAM, economic impact and losses due to RAM, but also new means to fight it in the world.